2020
DOI: 10.1155/2020/3530296
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Cardiac Protection Conferred by Proanthocyanidins in Grape Seeds against Development of Ehrlich Solid Tumors in Mice

Abstract: Examination of the antineoplastic effects of a range of chemical compounds is often undertaken via the transplantable tumor model of Ehrlich solid tumor (EST), which is a simulation of breast cancer. The purpose of this study was to explore how cardiac toxicity, damage, oxidative stress, and changes in the expressions of TNFα and apoptotic P53 triggered by EST could be countered with grape seed proanthocyanidins (GSPE). To that end, 50 female mice were used, with arbitrary and equal distribution into five grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
3
4
0
Order By: Relevance
“…Cancer cells elicit free radicals to be shaped in excess, destructive lipids, and theoretically generating lipid peroxidation [19], which may be the cause for the notable upsurge in the levels of cardiac MDA persuaded by the EAC group in this study. These findings are also consistent with the results of Aldubayan [20] who revealed that the EAC cells injected into mice showed a significant decrease in TAC and a significant increase in the level of malondialdehyde in the heart tissues. In addition, the results of this study are in good agreement with the results of Joukar et al [21], who showed that MDA levels in the liver, kidneys, and testes are increased due to the formation of EAC tumors.…”
Section: Discussionsupporting
confidence: 92%
“…Cancer cells elicit free radicals to be shaped in excess, destructive lipids, and theoretically generating lipid peroxidation [19], which may be the cause for the notable upsurge in the levels of cardiac MDA persuaded by the EAC group in this study. These findings are also consistent with the results of Aldubayan [20] who revealed that the EAC cells injected into mice showed a significant decrease in TAC and a significant increase in the level of malondialdehyde in the heart tissues. In addition, the results of this study are in good agreement with the results of Joukar et al [21], who showed that MDA levels in the liver, kidneys, and testes are increased due to the formation of EAC tumors.…”
Section: Discussionsupporting
confidence: 92%
“…Our results bid that treatment with the sodium salt of the tested compound displayed a highly considerable diminish in the concentration of urea to 30. These results are consistent with those reported by Aldubayan,48 who reported that Ehrlich ascites carcinoma was related to high levels of cardiac enzymes LDH and CK-MB in the serum, supplying proof that cardiac dysfunction occurred in Ehrlich-bearing mice.…”
Section: Ta B L E 1supporting
confidence: 93%
“…In addition, GSE prevented excessive ROS accumulation in heart tissue and might increase antioxidant capacity. Moreover, GSE had scavenging properties that reduced the free radicals (Aldubayan, 2020 ; Belviranlı et al., 2012 ). In addition, our data revealed that exercise training with different intensities (low, moderate, and high) increased the relative expression of Mapk3 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Aldubayan indicated that GSE consumption significantly decreased creatine phosphokinase, lactate dehydrogenase, creatine kinase as biochemical cardiac markers. Hence, cardiac injuries were reversed by GSE consumption (Aldubayan, 2020 ).…”
Section: Discussionmentioning
confidence: 99%